2017
DOI: 10.1038/s41467-017-00401-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular-matrix-mediated osmotic pressure drives Vibrio cholerae biofilm expansion and cheater exclusion

Abstract: Biofilms, surface-attached communities of bacteria encased in an extracellular matrix, are a major mode of bacterial life. How the material properties of the matrix contribute to biofilm growth and robustness is largely unexplored, in particular in response to environmental perturbations such as changes in osmotic pressure. Here, using Vibrio cholerae as our model organism, we show that during active cell growth, matrix production enables biofilm-dwelling bacterial cells to establish an osmotic pressure differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
152
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(168 citation statements)
references
References 67 publications
14
152
2
Order By: Relevance
“…For K. pneumoniae, lowering the agar concentration allowed the wild-type to colonize 445 more area, which was similar to how a rugose strain of V. cholerae that hypersecretes ECM 446 formed larger colonies on lower concentrations of agar [25]. In V. cholerae, it was 447 demonstrated that matrix secretion generates an osmotic pressure gradient between the agar 448 and the biofilm, allowing the biofilm to expand by physical swelling and increased nutrient 449 uptake.…”
Section: Momeni Et Al [21] Where a [~~] B Indicates A Neutral Intementioning
confidence: 83%
See 3 more Smart Citations
“…For K. pneumoniae, lowering the agar concentration allowed the wild-type to colonize 445 more area, which was similar to how a rugose strain of V. cholerae that hypersecretes ECM 446 formed larger colonies on lower concentrations of agar [25]. In V. cholerae, it was 447 demonstrated that matrix secretion generates an osmotic pressure gradient between the agar 448 and the biofilm, allowing the biofilm to expand by physical swelling and increased nutrient 449 uptake.…”
Section: Momeni Et Al [21] Where a [~~] B Indicates A Neutral Intementioning
confidence: 83%
“…When the two were co-cultured together, the NMV 257 covered less area, ~4 mm 2 , compared to when grown alone, ~12 mm 2 , at 24 h, but there was 258 no change at 48 h. The area covered by the NMV was also decreased when paired with P. 259 protegens, however, neither of these differences persisted at 48 h. In contrast, the area 260 covered by P. aeruginosa was decreased when grown in the presence of the K. pneumoniae 261 NMV at 24 h but not 48 h. When paired with P. aeruginosa, the area covered by the NMV 262 was not significantly increased as was observed for the parental K. pneumoniae strain when 263 paired with P. aerguinosa. The percentage of agar influences motility, as lower percentages enable swarming 290 and/or swimming motility and affect the colony growth of highly mucoid strains [25]. 291…”
Section: Co-cultures With a Non-mucoid K Pneumoniae Variant 246mentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases, an interplay between mechanical constraints and biological organization sets limits on the overall colony morphology and expansion dynamics [9]. The forces driving colony expansion are generated by non-homogeneous patterns of biological activity, originating from spatial localizations in cell growth and division [10], extracellular polymer matrix production [11][12][13], osmolyte secretion [14] and active stresses [15,16]. Conversely, the formation of localized biologically active zones is tightly coupled to the heterogeneity of the environment, including the diffusion and transport of nutrients [17], accumulation of metabolic by-products [18,19] and presence of quorum sensing and signaling agents that regulate cell-differentiation and development.…”
Section: Introductionmentioning
confidence: 99%